CYTOLOGIC EXAMINATION IN THE DIAGNOSIS OF ENDOMETRIAL CANCER (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Combined cytological examination of endometrial material, which includes the combined use of traditional, liquid cytology and immunocytochemical research methods, correlates with the results of histological examination and leads to a decrease in the amount of uninformative material, compared with the use of traditional and liquid cytology separately, which increases the efficiency and accuracy of diagnosis in atypical hyperplasia and endometrioid adenocarcinoma.